Pembingkaian Bobby Nasution pada SINDOnews.com dalam Mengatasi Banjir dan Kemacetan di Kota Medan - Syafruddin Pohan; Ratna Sari; Maisyarah Maisyarah (MUKASI: Jurnal Ilmu Komunikasi, 2023)
The rapidly developing digital era has given birth to online media, online media is now the choice because of the ease and speed of accessing it, only with gadgets and the internet, the information needed is immediately available. The source of this research comes from the online media site SINDOnews.com whose focus is related to news related to Bobby Nasution's leadership as the Mayor of Medan in overcoming the problems of flooding and traffic jams that have occurred in Medan City. This study aims to find out Robert Entman's framing analysis when framing news about Bobby Nasution on the online media SINDOnews.com in dealing with flooding and traffic jams in the city of Medan. Framing analysis by Robert Entman contains four main objectives, including defining the problem, diagnosing the causes of the problem, making moral judgments, and providing treatment recommendations. The methodology used in this study uses a qualitative descriptive methodology. The results of this study indicate the framing of Bobby Nasution at SINDOnews.com in overcoming floods and congestion in Medan City, namely that Bobby Nasution as the Mayor of Medan adopted a policy, namely that in dealing with flooding, he will use the retention aspect technology to prevent flooding, and in dealing with congestion, handling is carried out through construction of underpasses.